Impact of Endourological Techniques (PCNL and URS) on Kidney Function - Muhammad Saleem, Muhammad Islam, Muhammad Shahid Bhatti, Haris Hamid, Hassan Raza Asghar, Bilal Suria, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The presence of upper kidney and ureteric stones leads to urinary tract obstruction which, if untreated, can severely damage the kidneys. These organs, critical for homeostatic functions, undergo irreversible damage if the stones are not treated in a reasonable timeframe. Advancing modern techniques such as Percutaneous Nephrolithotomy (PCNL) and Ureterorenoscopy (URS) have made the field of urology more effective, streamlined, and less invasive. With that said, caution must be exercised when evaluating the impact of such techniques on renal function over the short term. The primary focus of this research surgery was to assess the differences in laboratory test results to evaluate renal function before and after PCNL and URS. Methods: The research encompassed patients who had a PCNL or URS procedure performed on them within a one-year timeframe and study was conducted at the Department of Urology and Renal Transplantation, Pir Abdul Qadir Shah Institute of Medical Sciences, Gambat, from May 2022 to April 2023. There were 67 patients in total and their kidney function was assessed via serum creatinine, eGFR, and blood urea nitrogen levels. These values were captured prior to the operation and 48-72 hours post-operatively. The changes in these parameters were analyzed statistically to assess their significance. Results: The study found a slight yet statistically meaningful improvement in renal function postoperatively. Patients who underwent PCNL showed more prominent changes, especially those with larger stones. No complications were reported that adversely affected renal function. Conclusion: Both PCNL and URS procedures relieve the burden of kidney stones while simultaneously demonstrating enhancement in renal function over a sustained period. Both methods are effective in the management of urolithiasis with appropriate patient selection and careful surgical management. Keywords: Kidney Stones, PCNL, URS, Renal Function, eGFR, Urology, Stone Removal, Serum Creatinine.